INDEPENDENSI AUDITOR, PEMAHAMAN GOOD GOVERNANCE DAN KUALITAS AUDIT: BUKTI PADA KANTOR AKUNTAN PUBLIK DI WILAYAH BEKASI - Siti Nurlatifah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
The purpose of this study was to determine the existence of (1) the impact of auditor independence on the audit quality of public accounting firms in the Bekasi area, (2) the impact of good governance on the audit quality of public accounting firms in the Bekasi area. This study uses a quantitative method with a deliberate sampling technique to choose the use used, namely 60 samples selected by KAP in the Bekasi area. The data collection technique in this study used a questionnaire method which was distributed directly to auditors working at Public Accounting Firms in the Bekasi area. The data were analyzed using multiple regression analysis using SPSS version 25. The results of this study are (1) auditor independence has a positive and significant effect on the audit quality of KAP in the Bekasi area. (2) The understanding of good governance has no effect on the audit quality of KAP in the Bekasi area.